An open-source tool to assess the carbon footprint of research. (1st September 2022) - Mariette, Jérôme; Blanchard, Odile; Berné, Olivier; Aumont, Olivier; Carrey, Julian; Ligozat, AnneLaure; Lellouch, Emmanuel; Roche, Philippe-Emmanuel; Guennebaud, Gaël; Thanwerdas, Joel; Bardou, Philippe; Salin, Gérald; et al.
Abstract: The scrutiny over the carbon footprint of research and higher education has increased rapidly in the last few years. This has resulted in a series of publications providing various estimates of the carbon footprint of one or several research activities, principally at the scale of a university or a research center or, more recently, a field of research. The variety of tools or methodologies on which these estimates rely unfortunately prevents any aggregation or direct comparison. This is because carbon footprint assessments are very sensitive to key parameters (e.g., emission factors) or hypotheses (e.g., scopes). Hence, it is impossible to address fundamental questions such as: is the carbon footprint of research structurally different between disciplines? Are plane trips a major source of carbon emissions in academic research? Massive collection and curation of carbon footprint data, across a large array of research situations and disciplines, is hence an important, timely and necessary challenge to answer these questions. This paper presents a framework to collect and analyse large amounts of homogeneous research carbon emission data in a network of research entities at the national scale. It relies on an open-source web application, GES 1point5, designed to estimate the carbon footprint of a department, research lab or team in any country of the world. Importantly, GES 1point5 is also designed to aggregate all input data and corresponding GHG emissions estimates into a comprehensive database. GES 1point5 therefore enables (i) the identification of robust local or national determinants of the carbon footprint of research and (ii) the estimation of the carbon footprint of the entire research sector at national scale. A preliminary analysis of the carbon footprint of more than one hundred laboratories in France is presented to illustrate the potential of the framework. It shows that the average emissions are 479 t CO2 e for a research lab and 3.6 t CO2 e for an average lab member (respectively 404 and 3.1 t CO2 e without accounting for the indirect radiative effects of aviation), with the current scope of GES 1point5 . Availability and implementation: GES 1point5 is available online at http://labos1point5.org/ges- 1point5 and its source code can be downloaded from the GitLab platform at https://framagit.org/ labos1point5/l1p5-vuejs .